State of rebellion: violence and intervention in the Central African Republic - Lombard, Louisa (African Arguments, 2016)
Introduction. - 1. Conflict and the State in the Peace-Kept World. - 2. The Nativeness of 'Foreign' Violence. - 3. Mobility as Power. - 4. Long and Short Histories of Rebellion. - 5. DDR and the Frustration of Desires for Entitlement. - 6. War as the Violence of the Pack. - 7. World Champion of Peacekeeping. - Conclusion